2018
DOI: 10.1016/j.cmi.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic factors affecting Clostridium difficile recurrence

Abstract: rCDI is a significant challenge for healthcare professionals, requiring a multifaceted approach; optimized infection control to minimize reinfection; C. difficile-targeted antibiotics to minimize dysbiosis; and gut microflora restoration to promote colonization resistance. These elements should be informed by our understanding of the microbiologic factors involved in both C. difficile itself and the gut microbiome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 100 publications
0
39
0
3
Order By: Relevance
“…Furthermore, ciprofloxacin, another efficient treatment for pouchitis, might be more effective in treating Fusobacteria than Bacteroidetes, based on MIC measurements [22]. In other circumstances, the sparing of anaerobic bacteria, such as Bacteroidetes, in the gut results in a higher clinical efficacy of antibiotic drugs used for gastrointestinal infections, e.g., it has been found to be important to preserve microbiota diversity when treating Clostridium difficile infection (CDI), so as to reduce the risk of recurrences [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ciprofloxacin, another efficient treatment for pouchitis, might be more effective in treating Fusobacteria than Bacteroidetes, based on MIC measurements [22]. In other circumstances, the sparing of anaerobic bacteria, such as Bacteroidetes, in the gut results in a higher clinical efficacy of antibiotic drugs used for gastrointestinal infections, e.g., it has been found to be important to preserve microbiota diversity when treating Clostridium difficile infection (CDI), so as to reduce the risk of recurrences [23].…”
Section: Discussionmentioning
confidence: 99%
“…If conditions are favorable, e.g., after antibiotic-induced dysbiosis when the reduced microbiome fails to convert primary bile acids into secondary bile acids, C. difficile spores are able to germinate to successively colonize the large intestine ( Theriot et al, 2014 ; Pike and Theriot, 2020 ). Even though antibiosis mostly stops the acute infection, C. difficile spores as well as some vegetative cells survive in the intestine and can subsequently cause a relapse as soon as antibiotic concentrations are sufficiently low ( Goulding et al, 2009 ; Chilton et al, 2018 ; Castro-Córdova et al, 2020 ; Feuerstadt et al, 2021 ; Normington et al, 2021 ). Initially, sporulation was assumed to be one of the major prerequisites for C. difficile’s persistence under clinical circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, antibiotics represent the single greatest risk factor for the development of CDI, 19 , 20 given the ability of CD to expand its population in a dysbiotic gastrointestinal tract. 21 , 22 Even the use of recommended CD-directed antibiotics may exacerbate intestinal dysbiosis, 23 , 24 and multiple studies have demonstrated that commensal microorganisms may not return to “baseline” after CDI. 25 , 26 These effects from conventional antibiotics require more study in human subjects to evaluate whether they contribute to persistence or recurrence of CDI, though the often-long-lasting gut ecological disturbances invoked by conventional antibiotics represent a potential, clinically relevant unintentional consequence of therapy.…”
Section: Challenges To Conventional Antibiotic Therapies For mentioning
confidence: 99%